Linking entrepreneurial orientation and business performance: the examination toward performance of cooperatives firms in northern region of Peninsular Malaysia - Dzulkarnain, Musa (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis (UniMAP), 2015)
Link to publisher's homepage at http://ijbt.unimap.edu.my/